2011
DOI: 10.1080/15374416.2011.563471
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Contexts and Their Effects on Clinicians' Impressions of Conduct Disorder Symptoms

Abstract: The purpose of this study was to examine whether contextual information about patients' clinical presentations affected clinicians' judgments of conduct disorder symptoms. Forty-five clinicians read vignettes describing hypothetical patients who displayed one conduct disorder symptom alongside information about the patients' home, school, and peer contexts. Clinicians judged the likelihood of patients meeting conduct disorder criteria. Contextual information highly affected judgments and these effects varied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 5 publications
4
58
3
1
Order By: Relevance
“…In conjunction with previous work examining the influence of explanatory life event context on assessments of conduct disorder and artificial disorders, [35][36][37][38]40,41 clinical psychologists are consistently influenced by explanatory context across disorders in assessment, even when the DSM is inconsistent in its treatment of explanatory context between disorders (e.g., between MDD and PTSD, in which a traumatic life event is one of the formal criteria for diagnosis 43 ). As argued in previous work, 57 although the DSM is often predominantly descriptive, clinical psychologists seem to push beyond the surface and incorporate causal factors into their assessments.…”
Section: Discussionmentioning
confidence: 94%
“…In conjunction with previous work examining the influence of explanatory life event context on assessments of conduct disorder and artificial disorders, [35][36][37][38]40,41 clinical psychologists are consistently influenced by explanatory context across disorders in assessment, even when the DSM is inconsistent in its treatment of explanatory context between disorders (e.g., between MDD and PTSD, in which a traumatic life event is one of the formal criteria for diagnosis 43 ). As argued in previous work, 57 although the DSM is often predominantly descriptive, clinical psychologists seem to push beyond the surface and incorporate causal factors into their assessments.…”
Section: Discussionmentioning
confidence: 94%
“…These findings from De Los Reyes and Marsh (2011) indicated that trained judges of patients’ behavior attend to the contexts surrounding patients’ clinical presentations when providing reports about patients’ behavior. Thus, the findings raise the question as to whether discrepancies between untrained informants’ reports might be explained, in part, by differences between informants in the contexts within which they observe behaviors about which they provide reports.…”
Section: The Operations Triad Model (Otm): a Framework For Interpretimentioning
confidence: 94%
“…For instance, De Los Reyes and Marsh (2011) presented clinicians with vignettes of children described as living in contexts that either posed risk for a conduct disorder diagnosis (e.g., exposure to parental psychopathology and poor peer relations) or contexts posing no such risk. Clinicians provided ratings of the likelihood that a comprehensive clinical evaluation of the child would suggest that the child meets criteria for a conduct disorder diagnosis.…”
Section: The Operations Triad Model (Otm): a Framework For Interpretimentioning
confidence: 99%
“…In support of this theoretical work, studies of participants ranging from preschool to adulthood have demonstrated that greater informant discrepancies relate to increased variation in the contexts within which participants express the behaviors being assessed (De Los Reyes, Bunnell, & Beidel, 2013; De Los Reyes, Henry, Tolan, & Wakschlag, 2009; Hartley, Zakriski, & Wright, 2011). Further, experimental work indicates that trained judges of children’s behavior (i.e., clinicians) attend to contextual information (e.g., environmental risk factors of childhood psychopathology) when providing reports about such behavior (De Los Reyes & Marsh, 2011). Additional experimental work indicates that parents and adolescents can be trained to incorporate information about the contexts within which specific behaviors occur when providing reports about these behaviors (De Los Reyes, Ehrlich et al, 2013).…”
mentioning
confidence: 99%